Managerial Performance Improvement Through Accounting Management Information and Business Strategy - Shahab, Ali (Jurnal Trikonomika, 2012)
The national and global economic conditions that have high uncertainty makes the company, must be able to compile reliable accounting information in an effort to solve the next problem of corporations and development firms. The strategy with appropriate information will give the higher information in corporate strategy. The problem is whether the variable business strategy can moderate the relationship between accounting information and managerial performance. This research is explanatory research by using quantitative approach with the multiregression model. The population in this study is all big manufacturing companies in Semarang with 54 companies as a sample. The results of this study revealed that the accounting information in the company gives effect to increase managerial performance. Business strategy can moderate the influence of accounting information on managerial performance. Prospector business strategy tends to increase the influence of accounting information on managerial performance.